Programa de orientação não presencial de pais de crianças deficientes auditivas. - Motti, Telma Flores Genaro (2005)
The final result of rehabilitation of hearing impaired children depends on how the parents deal with the situation, i.e. how they accept their child s condition and enjoy the opportunities of the environment to stimulate and optimize the therapeutic and educational work done by specialists. The information that parents receive should consider the social and emotional context, to allow application of orientations and exploitation of the available resources. The purpose of this work was to elaborate and evaluate a non-presential orientation program for parents and caretakers of children with severe or deep hearing impairment, aged 2 to 6 years. The program was designed in four units of theoretical content with basic information and proposals of practical activities, was applied to 30 parents assisted at the Center for Hearing, Language and Vision Disturbances of HRAC/USP. The units were prepared on the basis of information achieved from specialists and parents. Information from specialists comprised the orientation they provide during the appointments for hearing impairment diagnosis and hearing aid fitting, and the knowledge that parents should acquire from the orientation, in accordance with their reports. Information from the parents addressed their difficulties with the children, themselves and their family, and the type of information they would like to receive. To evaluate the content and the receptivity of the program, the parents answers to the questionnaires of the four units were considered, as well as the final interview, which was applied to the first 14 parents completing the questionnaires. The analyses revealed that parents look for clear and direct information, which may guide them in daily life, as well as suggestions of practical activities adequate to their real lives and families, to help in child development. Although some parents found difficulties in expressing themselves by writing or doing the activities that required some educational level, it was noticed that it did not impair a program with written material and suggestions of activities. It should be considered that some questions only aimed at making parents think about the proposed subjects, and even when having difficulties to answer some question or perform some activity, the parents were already involved with the subjects and could attempt to apply them to their reality, to make decisions with tranquility and confidence.